THE ROLE OF UZBEK NATIONAL VALUES IN URBAN AESTHETICS - Akramov Kozimjon Ibragimjon o‘g‘li (American Journals Publishing, 2025)
This article explores the integration of Uzbek national values into the aesthetic formation of urban environments. The study analyzes how traditional cultural elements, architectural patterns, and historical heritage influence modern urban planning in Uzbekistan. The research highlights the balance between modernization and cultural continuity, emphasizing how national identity shapes aesthetic perception and the sustainability of urban design.
Keywords: Uzbek national values, urban aesthetics, architecture and culture, traditional design, modern city planning, cultural heritage, identity in architecture, urban development, harmony and proportion, sustainable urban design.